Facial Palsy as Initial Symptom in Glycine Receptor Antibody Positive Progressive Encephalomyelitis With Rigidity and Myoclonus: A Case Report - Wang, Li; Zhang, Rui; Liu, Kai; Xu, Yafang; Song, Bo; Xu, Yuming (Frontiers in Neurology, 2022)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare and disabling syndrome characterized by painful spasms, myoclonic jerks, hyperekplexia, brainstem signs and dysautonomia, which is considered to be a severe form of stiff person spectrum disorder（SPSD）and is mostly associated with glycine receptor antibodies. PERM has an acute or subacute course with complex and varied initial symptoms mainly manifested as stiffness and pain. The authors present the case of a male patient admitted for intractable stiffness and paroxysmal myoclonus of the lower extremities preceded by 5 days history of facial palsy. After admission, his symptoms deteriorated rapidly. He developed progressive generalised hypertonia and painful spasms quickly spread to the upper extremities and he suffered frequent paroxysmal myoclonus. Serum and CSF were tested by cell-based assay and found to be positive for glycine receptor antibodies(GlyR-Abs). The patient developed complications such as crushed teeth, lumbar vertebral compression fractures and psoas major muscle abscess during rapid disease progression though he responded well after treated with intravenous methylprednisolone and immunoglobulin. This report of PERM initiated as facial palsy followed by acute progression helps to expand the clinical spectrum of this rare autoimmune disorder and raise awareness of prevention of complications.